Climate change mitigation with technology spillovers - Foucart, Renaud; Garsous, Grégoire (Springer, 2017)
We explore the implications of an increase in clean technology spillovers between developed and developing countries. We build a game of abatements in which players are linked with technology spillovers determined by an initial choice of absorptive capacities by developing countries. We show that, within a non-cooperative framework, the response of clean technology investments in developed countries to an increase in cross-country technology spillovers is ambiguous. If the marginal benefits of these additional abatements are not sufficiently high, developed countries have a strategic incentive to decrease investments. Such a strategic response jeopardizes the initial effects of an increase in technology spillovers on climate change mitigation and decreases the incentives for developing countries to enhance their absorptive capacities.